Role of endocannabinoid neurotransmission in the insular cortex on cardiovascular, autonomic and behavioral responses evoked by acute restraint stress in rats - Belem-Filho, Ivaldo J.A.; Godoy, Ana C.V.; Busnardo, Cristiane [UNESP]; Frias, Alana T.; Zangrossi, Helio; Del Bianco Borges, Bruno; Herval, Ana C.F.; Correa, Fernando M.A.; Crestani, Carlos C. [UNESP]; Alves, Fernando H.F. (Elsevier, 2025)
This study aimed to investigate the role of endocannabinoid mechanisms present within the insular cortex (IC) on cardiovascular, autonomic and anxiogenic-like responses evoked by an acute session of restraint in rats. For this, bilateral guide cannulas directed to the IC were implanted in male Wistar rats for intrabrain microinjection of the selective CB1 receptor antagonist AM251, the selective TRPV1 receptor antagonist capsazepine, the fatty acid amide hydrolase (FAAH) inhibitor URB597 or the monoacylglycerol lipase (MAGL) inhibitor JZL184. The effects of pharmacological treatments were evaluated on restraint-evoked increases in blood pressure and heart rate, sympathetically-mediated cutaneous vasoconstriction and in delayed anxiogenic-like effect assessed 24h after stress exposure in the elevated plus maze (EPM) and open field (OF). We observed that acute restraint stress decreased the exploration of both EPM open arms and OF center region in animals treated with vehicle into the IC, thus indicating an anxiogenic-like effect. Inhibition of MAGL within the IC evoked by local treatment with JZL184 avoided the restraint-evoked anxiogenic effect. IC treatment with JZL184 also attenuated the tachycardia during restraint. The other pharmacological treatments did not modify the cardiovascular, autonomic and behavioral responses evoked by restraint. Taken together, these findings suggest that endocannabinoid neurotransmission in the IC, potentially acting through the endocannabinoid 2-arachidonoylglycerol, plays an inhibitory role in both tachycardia and anxiogenic-like effect evoked by stressful events.
Keywords: Emotional stress; Endocannabinoids; Insular cortex; Sympathetic activity